(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
The Experiment was conducted to establish an efficient plant regeneration protocol from hypocotyl sections of soybean. Callus initiation, shoot and root development were observed by using different concentrations and combinations of growth regulators. The best result for callus induction was observed in MS medium supplemented with 1.5 mg/l Kinetin and 2.0 mg/l NAA. The calli were transferred to shoot induction medium. The best shoot induction occurred in the medium containing 3.0 mg/l BAP and 0.5 mg/l NAA. The elongated shoots developed roots on MS medium supplemented with different IBA concentrations where 1.5 mg/l IBA was the best for root development. Plantlets with a well developed root system were transplanted in plastic container with a soil mixture of cowdung and fine sand. Plantlet survival rate was 70%. Through this experiment, a general suitable regeneration protocol from hypocotyls of soybean has been developed which can potentially be used for micropropagation and future transformation research in soybean. DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17049